Anti-Gout Effects of the Medicinal Fungus Phellinus igniarius in Hyperuricaemia and Acute Gouty Arthritis Rat Models - Li, Hongxing; Zhang, Xinyue; Gu, Lili; Li, Qín; Ju, Yue; Zhou, Xuebin; Hu, Min; Li, Qīn (Frontiers in Pharmacology, 2022)
Background: Phellinus igniarius (P. igniarius) is an important medicinal and edible fungus in China and other Southeast Asian countries and has diverse biological activities. This study was performed to comparatively investigate the therapeutic effects of wild and cultivated P. igniarius on hyperuricaemia and gouty arthritis in rat models. Methods: UPLC-ESI-qTOF-MS/MS was used to identify the chemical constituents of polyphenols from wild P. igniarius (WPP) and cultivated P. igniarius (CPP). Furthermore, WPP and CPP were evaluated in an improved hyperuricaemia rat model induced by yeast extract, adenine and potassium oxonate, which was used to examine xanthine oxidase (XO) activity inhibition and anti-hyperuricemia activity. WPP and CPP therapies for acute gouty arthritis were also investigated in a monosodium urate (MSU)-induced ankle swelling model. UHPLC-QE-MS was used to explore the underlying metabolic mechanisms of P. igniarius in the treatment of gout. Results: The main active components of WPP and CPP included protocatechuic aldehyde, hispidin, davallialactone, phelligridimer A, hypholomine B and inoscavin A as identified by UPLC-ESI-MS/MS. Wild P. igniarius and cultivated P. igniarius showed similar activities in reducing uric acid levels through inhibiting XO activity and down-regulating the levels of UA, Cr and BUN, and they had anti-inflammatory activities through down-regulating the secretions of ICAM-1, IL-1β and IL-6 in the hyperuricaemia rat model. The pathological progression of kidney damage was also reversed. The polyphenols from wild and cultivated P. igniarius also showed significant anti-inflammatory activity by suppressing the expression of ICAM-1, IL-1β and IL-6 and by reducing the ankle joint swelling degree in an MSU-induced acute gouty arthritis rat model. The results of metabolic pathway enrichment indicated that the anti-hyperuricemia effect of WPP was mainly related to the metabolic pathways of valine, leucine and isoleucine biosynthesis and histidine metabolism. Additionally, the anti-hyperuricemia effect of CPP was mainly related to nicotinate and nicotinamide metabolism and beta-alanine metabolism. Conclusions: Wild P. igniarius and cultivated P. igniarius both significantly affected the treatment of hyperuricaemia and acute gouty arthritis models in vivo and therefore may be used as potential active agents for the treatment of hyperuricaemia and acute gouty arthritis.